Nurturing Soft Skills in Moroccan Early Childhood Care and Education A Systematic Review - Riham , BELKBIR; Sanae, ACHAG (Revue Internationale du Chercheur, 2023)
In the current global environment, it is alleged that theoretical knowledge is not sufficient for the accomplishment of an individual in the workplace. The idea of someone 'going soft' does not have absurdly definite connotations for adult learners, but when it comes to children; softness is a pivotal pattern of their learning and development. Children need to be indoctrinated to address the "traps" of life, have critical thinking, control their feelings and their relationships with others, and be able to voice their ideas and defend their position with arguments. To the advantage of the knowledge gained of the need to develop “soft” skills from a young age, it is indispensable that Moroccan preschools introduce a module on the most important soft skills that children can form. A systematic literature review is conducted to provide an extensive overview of empirical studies measuring the importance of 21st century skills. The article discusses the current situation of Moroccan early childhood education and the opportunities for the development of soft skills from preschool age. The main results of this literature review highlight the importance of efforts to promote soft skills in the arena of early childhood education in Morocco.